Can establishing the National Big Data Comprehensive Experimental Zone promote green low-carbon development? Evidence from China - Yao, Yushan; Wang, Zhe; Cao, Shanshan (Frontiers in Environmental Science, 2025)
The rapid development of digital economy provides necessary technical support for green and low-carbon transformation, and it is of great significance to explore the impact of digital economy on green and low-carbon development for the sustainable development of the economy and society. Balanced panel data of 30 provinces and cities from 2005 to 2021 are used to construct a dual machine learning model for empirical analysis. It is found that digital economic development can reduce the regional carbon emission intensity and promote green and low-carbon development. The mechanism test shows that digital economic development significantly promotes regional green low-carbon development through the knowledge spillover dimension. The heterogeneity analysis shows that the level of green low-carbon development in the central region is significant at the 1% level, while the levels in the eastern and western regions are not significant. A government with less fiscal pressure has a more significant effect on green low-carbon development.